Improved Knowledge of Children and Parents after Education on Good Gadget Utilization - Ni Putu Emy Darma Yanti (Jurnal Peduli Masyarakat, 2020)
The phenomenon of using gadgets among school-age children is increasing. One of the factors that causes it is the lack of assistance from parents in terms of using gadgets in children. In addition, the lack of understanding by parents regarding the use of healthy gadgets for children also has an impact on children's psychosocial development. This service activity is carried out in the form of providing education which aims to increase the knowledge of children and parents about the use of good gadgets in Penglipuran Village, Bangli Regency, Bali. Education was held on the fourth week of October 2018 which was attended by 35 children and 25 parents. The method used was lectures and discussions each for 60 minutes and giving leaflets. The children's and parents' knowledge was used using a questionnaire given before and after educational activities. Data analysis used the univariate test to describe the mean value of the level of knowledge of children and parents before and after education. The results of the questionnaire analysis showed an increase in children's knowledge from five to eight and parents' knowledge from five to nine after being given education. The results of the service activities concluded that there was an effect of providing education on the level of knowledge of children and parents about the use of good gadgets.